Penerapan Biophilic Design untuk Peningkatan Kualitas Ruang di Taman Pendidikan Al-Qur’an Amaliyah - Dina Fatimah; Lia Warlina; Kankan Kasmana; Deni Albar; Febry Maharlika (LPPM UNINUS, 2021)
The goal of this PKM program is to use a Biophilic Design approach to improve the quality of space in educational facilities. Biophilic Design is a concept that uses natural elements to create physical and psychological comfort. As a Community Service (PKM) partner, the Faculty of Design joins the Amaliyah Quran Education Park, Campaka Village, Andir District, Bandung City. The method used is to identify the target audience, the types of activities, and the stages of implementation. Carry out the process of designing room facilities that encourage the improvement of the quality of learning. The satisfaction of partners with the changes made demonstrates the effectiveness of this service. The activities include the installation of sanitation facilities, the addition of vegetation, and the design of comfortable study rooms. Partners benefit greatly from assistance in providing public facilities in this educational space. Learning at the TPA becomes more conducive with the addition of sanitation facilities, and the comfort of students and teachers is fulfilled by this program.